MODIS satellite based net primary productivity of natural rubber in traditional growing region of India - James Jacob, Shankar Meti and (Journal of Plantation Crops, 2018)
Net primary productivity (NPP), an indicator of ecosystem productivity is being assessed by field sampling technique or by gas exchange technique but are not ideal for regional level assessment/monitoring with spatial and temporal dimension. In this regard, satellite based NPP data are becoming the handier tool in monitoring and assessment of ecosystem performance spatially and temporally at regional and global level in non-destructive and cost effective manner. This paper aims at understanding the variation in the productivity of rubber ecosystem by MODIS satellite based NPP data across the traditional belt of India and their relation with topography, soil and climatic factors of present as well as projected future climate. MODIS satellite based average annual NPP of rubber plantation was estimated as 10 tons C ha-1 year. Rubber NPP showed geographical variation across the traditional rubber belt showing significant negative correlation with latitude (r = -0.54) and positive correlation with longitude (r = 0.327). Mean diurnal temperature range, T-1 of warmest month, annual temperature range and annual precipitation showed significant negative correlation with rubber NPP. Soil management unit as well as moisture adequacy index showed significant effect on rubber NPP. Soil with high OC, less gravel and more depth showed better NPP. Rubber NPP showed a significant positive relation with soil moisture. Regression based model predicted declining trend of rubber NPP in southern region and increasing trend in central region under future climatic condition.The present study indicated significant influence of climate, topography and soil on rubber ecosystem.